Developing a Traceability System for Tuna Supply Chains - Bayu Ardy Kresna; Kudang Boro Seminar; Marimin Marimin (International Journal of Supply Chain Management, 2017)
Tuna is one of the flagship export commodity from Indonesia which has special characteristics such as high perishable food and has a complex supply chain network. According to the characteristics, the potency of deterioration and cross contamination along the chain will be a challenge for every actor in tuna supply chain, to provide tuna product with the best quality and safe to consume. One of the tool to ensure the standard safety and quality is doing traceability system along tuna supply chain. It is very crucial because every actor in chain has a responsibility to ensure food safety and quality through handling, manufacturing, packaging, and transporting the product. The critical point that should be covered by traceability system in tuna supply chain includes temperature, content of histamine, quantity of TPC, and contents of bacterial pathogens like Salmonella, and the sanitation for workers, equipment and processing room. The Information Technology (IT) based tuna traceability system is proposed and discussed in this paper to optimizing the traceability system in tuna supply chain. This paper discusses the development of a traceability system architecture and prototype for tuna supply chains. The developed system prototype shows the functional capabilities required for backward and forward tracing of tuna fish transformation and movement along the chain involving many actors (from fishing vessels to retailers). The system also permits the monitoring of processes and products based on microbiological analysis and on existing SOPs owned by some actors in a a tuna supply chain. The implementation issues are also described in this paper.